Prophylactic Mesh in Parastomal Hernia Prevention: Current Evidence - Elisa Mäkäräinen (Journal of Abdominal Wall Surgery)
IntroductionParastomal hernia (PSH) is a common long-term complication following stoma creation. The incidence of PSH exceeds 50% in long-term follow-up of end colostomy patients, while it remains lower in ileostomies and ileal conduit urinary diversions. PSH prevention strategies are of interest due to the poor outcomes and high recurrence rates associated with PSH repair.Overview of Techniques to Prevent PSHVarious technical approaches have been explored to reduce the risk of PSH. However, none have shown consistent benefit toward reducing PSH rate without the use of prophylactic mesh. The keyhole mesh technique was the first to demonstrate a significant reduction in PSH rates in early trials, but larger randomized controlled trials (RCTs) have later questioned its efficacy. The modified keyhole technique, using a funnel-shaped mesh, has shown promising results in recent small studies, with lower PSH incidence and potentially reduced stomal prolapse rate. Other methods such as the Sugarbaker technique and use of biological meshes in PSH prevention have been evaluated as well, with mixed results. While most research focuses on end colostomy, there is limited data on PSH prevention in ileostomies and ileal conduits.ConclusionDespite early enthusiasm, the keyhole technique has not proven to be effective in preventing PSH. The modified funnel-shaped mesh appears to be a promising development, though long-term outcomes are lacking. Preventive mesh placement is still supported by international guidelines; however, these recommendations are not widely followed in colorectal surgery departments. Thus, further research is essential to guide future recommendations for PSH prevention.